Tobacco Consumption and Mental Health in the Canary Islands: A Quantitative Analysis - Nieto-González, Imanol L.; Rodríguez-Donate, M. Carolina; Guirao-Pérez, Ginés (Frontiers in Public Health, 2022)
Although the detrimental health effects of tobacco, there has been scant research into determining comprehensive profiles to characterise individuals with a higher risk of smoking. This paper identifies such profiles and probabilistically quantifies the effects of certain traits on the decision to smoke in the Canary Islands. This characterisation is approached from a broad and novel point of view for the region studied, given that the analysis not only studies sociodemographic characteristics, lifestyle and health, but also incorporates mental health. The results show that suffering from some type of psychopathology leads to a higher probability of tobacco consumption. Moreover, just as the promotion of a healthy lifestyle has a direct impact on tobacco consumption, the implementation of public policies that reduce the risks of suffering from a mental illness could also reduce the prevalence of smoking in the region and contribute to the design of more effective prevention strategies.